2011
DOI: 10.1190/geo2010-0258.1
|View full text |Cite
|
Sign up to set email alerts
|

Source-rock seismic-velocity models: Gassmann versus Backus

Abstract: Source rocks are described by a porous transversely isotropic medium composed of illite and organic matter (kerogen, oil, and gas). The bulk modulus of the oil/gas mixture is calculated by using a model of patchy saturation. Then, the moduli of the kerogen/fluid mixture are obtained with the Kuster and Toksöz model, assuming that oil is the inclusion in a kerogen matrix. To obtain the seismic velocities of the shale, we used Backus averaging and Gassmann equations generalized to the anisotropic case with a sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 25 publications
0
50
0
14
Order By: Relevance
“…Sayers (2013) concluded that the kerogen in the Bakken reduces elastic stiffnesses when forms an interconnected network instead of discrete inclusions. Carcione et al (2011) indicated that if kerogen is treated as part of the solid skeleton, it is optional to model the effective moduli using Hashin-Shtrikman bounds (Hashin and Shtrikman, 1963). Although Gassmann's theory is frequently used for predicting elastic moduli, it is noteworthy that organic-rich rocks do not obey some basic assumptions of that theory (Gassmann, 1951;Mavko et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Sayers (2013) concluded that the kerogen in the Bakken reduces elastic stiffnesses when forms an interconnected network instead of discrete inclusions. Carcione et al (2011) indicated that if kerogen is treated as part of the solid skeleton, it is optional to model the effective moduli using Hashin-Shtrikman bounds (Hashin and Shtrikman, 1963). Although Gassmann's theory is frequently used for predicting elastic moduli, it is noteworthy that organic-rich rocks do not obey some basic assumptions of that theory (Gassmann, 1951;Mavko et al, 2009).…”
Section: Introductionmentioning
confidence: 97%
“…The Bakken shale is a case in point of rock physics of transversely isotropic source rocks (e.g. Carcione et al, 2011;Sayers, 2013;Vernik and Nur, 1992). Shale fabric is conceptualized as lenticular grains of illite rather than continuous sheets (Vernik and Landis, 1996;Vernik and Milovac, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported poroelastic constants of 0.3-0.6 and 0.1-0.8 for Haynesville and Bossier shales, respectively; the low values that are specific for stiff, low porosity rocks. Carcione et al (2011) theoretically studied effects of kerogen fraction and partial saturation on elastic properties of organicrich shales at different frequencies. Sayers (2013) used the database provided by Vernik and Liu (1997) to test three different effective medium theories.…”
Section: Introductionmentioning
confidence: 99%
“…The shale is composed of quartz, clay, carbonate, the mixture of kerogen and hydrocarbons, and fluid-saturated pores in the shale rock matrix. Elastic properties of the constituents and oil, gas, and water are given in Table 1 (Carcione et al 2011;Mavko et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the impact of kerogen on elastic properties and seismic responses of shales has received more interest. Carcione et al (2011) and Vernik and Milovac (2011) researched and compared rock physics models for organic-rich shales. Zou et al (2011) analyzed the capacity of reservoirs in terms of nano-porosity in kerogen in shales.…”
Section: Introductionmentioning
confidence: 99%